Peran DPRD Kota Kupang dalam Fungsi Pengawasan Kebijakan Kesehatan Ibu dan Anak yang Responsif Gender : Studi Kasus di Kecamatan Oebobo - Margaretha Bakang Hera; Rex Tiran; Diana S.A.N Tabun; Ananias R.P Jacob (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the role of the Kupang City Council in carrying out its supervisory function on gender-responsive maternal and child health policies, with a case study focus on Oebobo District. The background of this study stems from the high maternal and child mortality rates and the suboptimal implementation of Kupang City Regulation No. 7 of 2013. This study uses a qualitative approach with interview, observation, and documentation techniques, and involves informants from DPRD members, health workers, posyandu cadres, and community leaders. The results show that the DPRD, particularly through Commission IV, has carried out its supervisory function through regulatory support, budget allocation, program evaluation, and field visits. Some of the programs supervised include Free Nutritious Meals (MBG), strengthening Posyandu, and basic health services at Puskesmas. However, the effectiveness of supervision still faces various obstacles, including the lack of female representation in the DPRD, strong patriarchal culture, lack of socialization of local regulations, weak cross-sector coordination, and low community participation. The conclusion of this study confirms that the success of gender-responsive maternal and child health policies is greatly influenced by the capacity of the DPRD in oversight, political and budgetary support, and community involvement.